Implementing online learning of Diagnostic Criteria for the Temporomandibular Disorders (DC/TMD) protocol in undergraduate dental education - Malmberg, Jaana; Näpänkangas, Ritva; Liljeström, Marjo-Riitta; Tanner, Johanna; Teerijoki-Oksa, Tuija; Suominen, Auli; Sipilä, Kirsi (Taylor & Francis, 2025)
Introduction: The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) is part of the undergraduate dental curriculum. Online teaching has nowadays become common also in dentistry. Objective: To compare undergraduate students’ self-assessed ability and satisfaction with learning DC/TMD Axis I between traditional and online learning and to evaluate the possible gains of online teaching. Material and Methods: Third-year undergraduate dental students in 2018 (traditional learning, Group 1, n = 43/50) and in 2019 (online learning, Group 2, n = 34/50) at the University of Oulu, Finland evaluated their self-assessed ability and satisfaction with learning DC/TMD clinical examination and diagnostics on a 10-point scale. Additionally, those participating in online courses answered to two open-ended questions; Group 2 (n = 50) and another group from the University of Eastern Finland in 2019 and 2020 (n = 75, Group 3). Total of 105/125 students (84\%) responded. Content analysis was used to open-ended responses. Results: The online course reported significantly higher self-assessed ability in measurements (p = 0.004), identifying referred pain (p = 0.043) and statement for the diagnostics (p = 0.017) and also higher self-assessed satisfaction in measurements (p = 0.046). According to the content analysis, essential gains of online teaching were efficient learning, videos and exercises, and adjustability to own timetable. Conclusion: The online learning course can be considered as a good option for traditional learning of the DC/TMD protocol.